Tiktok sarana Belajar Pendidik PAUD Meningkatkan Kemampuan Meyiapkan Ragam Kegiatan Main - Andepi Daryana; Neng Delis (Idarotuna: Jurnal Manajemen Pendidikan Islam, 2024)
The research background is that the play activities, tools and materials prepared by teachers for children are not diverse. The aim of this research is to develop strategies, describe challenges and solutions and explore teachers' perceptions regarding the use of TikTok to increase the ability to prepare various children's play activities at SPS Al-Ikhlas Sawah Jalan, which is located at Kp. Sawah Jalan, Tanjung Jaya Village, Pakenjeng District, Garut Regency. The type of research used is descriptive qualitative research, the population of this research is all educators and early childhood education staff at SPS Al-Ikhlas Sawah Jalan, totaling three people, who are also the sample. The data collection techniques used by researchers in this research used observation, interviews and documentation. The instruments used by researchers in this research were the researchers themselves plus an interview guide, writing equipment and recording equipment. Analysis techniques start from data reduction, data display and drawing conclusions. The results of this research show that PAUD SPS Al-Ikhlas Sawah Jalan educators can use TikTok as a medium that can increase their ability to provide a variety of games, various tools and materials, which are presented in a way that attracts children's interest.